Short AntiMicrobial Peptides (SAMPs) as a class of extraordinary promising therapeutic agents. (July 2016) - Ramesh, Suhas; Govender, Thavendran; Kruger, Hendrik G.; de la Torre, Beatriz G.; Albericio, Fernando
Abstract : The emergence of multidrug resistant bacteria has a direct impact on global public health because of the reduced potency of existing antibiotics against pathogens. Hence, there is a pressing need for new drugs with different modes of action that can kill microorganisms. Antimicrobial peptides (AMPs) can be regarded as an alternative tool for this purpose because they are proven to have therapeutic effects with broad‐spectrum activities. There are some hurdles in using AMPs as clinical candidates such as toxicity, lack of stability and high budgets required for manufacturing. This can be overcome by developing shorter and more easily accessible AMPs, the so‐calledS hortA ntiM icrobialP eptides (SAMPs) that contain between two and ten amino acid residues. These are emerging as an attractive class of therapeutic agents with high potential for clinical use and possessing multifunctional activities. In this review we attempted to compile those SAMPs that have exhibited biological properties which are believed to hold promise for the future. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : This review presents more than forty sets of SAMPs (>400 no) along with their structure, function, activity and special characteristics. Together, these peptides illustrate the potential bioactivity, room for modification and highlights scope for further developments.